COASTAL ENVIRONMENTAL VULNERABILITY ON COASTAL CITIES IN INDONESIA - Adi Wibowo; Supriatna Supriatna (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2011)
Indonesia is known as a country with a strong in shipping, both nationally and internationally, which is shown by the number of coastal cities in Indonesia. Population growth in coastal cities in line with history of civilization who lived along the coast of Indonesia. Population growth led to expansion of the coastal cities in Indonesia, this increase affect land use change. Changes in land use, especially use of forest, will increase the use of setlement and agricultural caused an impact on increasing the contaminant throw into the river body or water body. Eventually cause contamination into the sea also increase, mainly going to affect the coastal environment around the coastal city. The objective is to find out coastal environmental vulnerability on coastal cities in Indonesia using spatial analysis method. First, count the number of population growth per year as index of population. Second, the number of land use change will be used as in index of change of land use. Third, count the number of river through the city and towards the sea coast, the results will show the index number of rivers. Index of population growth, land use change index and index number of rivers are combined and used to calculate the level of vulnerability of coastal environment around the coastal city spatially. The conclusion was that the higher the number of population growth, the higher of the landuse change and the most of rivers in the coastal city, that’s the higher the level of vulnerability of coastal environments.Keywords: coastal city, land use, river, environmental vulnerability